REPRESENTATION OF JAVANESE CULTURE IN THE RELIGIOUS FILM WHEN LOVE IS PRAISE 2 (Semiotic Analysis of Charles Sander Pierce) - Ido Afriadi; Namira Fitria; Parlin Harbet; Sanika Sembiring (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research is a research that analyzes Javanese cultural values in the religious cinema film When Love Recites Tasbih 2. The formulation of the problem in this research is what are the signs and meanings that represent Javanese cultural values in the cinema film When Love Recites Tasbih 2. This research uses data analysis, namely the meaning of symbols as a semiotic study. The method used is a qualitative descriptive method that shows the results of the research that emphasizes meaning rather than generalization. The data in this study presents verbal texts and nonverbal texts. Verbal texts are in the form of writing and speaking, while nonverbal texts are in the form of images or settings contained in the film. As for the data collection technique, the researcher used the note-taking technique in the form of (1) watching the film, (2) noting the things needed, (3) collecting (screen capture), (4) selecting, and (5) analyzing to obtain conclusions. The researcher used Charles Sanders Pierce’s semiotic study by focusing on the meaning of symbols as the data obtained. Furthermore, the data was analyzed to obtain the cultural values contained in the film. The researcher found 4 images and narratives that contain symbolic meanings related to Javanese cultural elements. Researchers found cultural values in the form of words and locations in Central Java.